2004
DOI: 10.1136/bmj.38111.639734.7c
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, shame, and blame experienced by patients with lung cancer: qualitative study

Abstract: Objectives To draw on narrative interviews with patients with lung cancer and to explore their perceptions and experience of stigma. Design Qualitative study. Setting United Kingdom. Participants 45 patients with lung cancer recruited through several sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
647
4
32

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(707 citation statements)
references
References 20 publications
(20 reference statements)
24
647
4
32
Order By: Relevance
“…Patients with certain types of cancer are more likely blamed when their illness is perceived to be caused by personal behaviors or (particularly disapproved) lifestyles (Chapple et al, 2004;Lebel and Devins, 2008;Shepherd and Gerend, 2013). Knowledge of the link between sexuality behavior and cervical cancer could increase the chances that women with cervical cancer may be stigmatized for their medical condition (Lebel and Devins, 2008;Shepherd and Gerend, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with certain types of cancer are more likely blamed when their illness is perceived to be caused by personal behaviors or (particularly disapproved) lifestyles (Chapple et al, 2004;Lebel and Devins, 2008;Shepherd and Gerend, 2013). Knowledge of the link between sexuality behavior and cervical cancer could increase the chances that women with cervical cancer may be stigmatized for their medical condition (Lebel and Devins, 2008;Shepherd and Gerend, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On certain occasions, the patients used this concept that there might be exceptions, in order to refute the medical fi nding that tobacco is the greatest cause of lung cancer. In this, their views coincided in some points with the fi ndings by Chapple et al 12 On this basis, they needed to formulate other hypotheses to explain the disease occurrence, albeit with low plausibility.…”
Section: Believe That With the Little That God Has For Me The 'Otmentioning
confidence: 87%
“…Recently, Chapple et al 12 designed a qualitative study to draw on narrative interviews with patients with lung cancer and also to explore their perceptions and experience of stigma. These authors observed that the participants experienced the feelings commonly felt by patients with other types of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Ces actions doivent s'intégrer dans les schèmes d'appréhension profanes, prismes au travers desquels les messages préventifs sont interprétés [11]. Notre enquête montre aussi la persistance de représentations péjoratives liées au cancer (qui peut avoir des effets délétères pour les personnes atteintes [12]), ainsi que la croyance en de multiples agents cancérigènes. Or, certaines de ces opinions peuvent freiner ou favoriser les comportements jugés favorables à la santé.…”
Section: Discussionunclassified